Analogies as a Potential for Expressing Creativity at Different Levels - Cvjetinovic, Vesna Z.; Pavlović, Zlatko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
People living in the modern world face an increasing number of serious problems, the solution to which requires a creative approach. Therefore, the issue of creativity development and the factors that influence it are becoming increasingly important, as is creativity research. The paper describes the basics of one of the models of creativity (the 4C model) as a model that can be used for a more comprehensive understanding of such a complex phenomenon as creativity. It then uses examples to demonstrate how analogies can be applied to each of the four levels of creativity described by the 4C model. Analogies can be a tool for encouraging creative problem-solving and behavior. This applies to all of the levels of creativity described. The pedagogical importance of creativity at the lower, initial levels (mini-c and little-c creativity), which serve as the foundation for the higher levels of creativity (Pro-c and Big-C creativity), was emphasized. In this context, emphasis was placed on teaching children how to understand, use, and create metaphors and analogies.